Tools and methods to support adaptive policy making in marine areas: Review and implementation of the Adaptive Marine Policy Toolbox. (1st January 2018) - Furlan, E.; Torresan, S.; Ronco, P.; Critto, A.; Breil, M.; Kontogianni, A.; Garmendia, M.; Pascual, M.; Sauzade, D.; Skourtos, M.; Marcomini, A.
Abstract: The development of adaptive policies for the management of dynamic and complex ecosystems, such as marine and coastal environments, asks for flexible and innovative tools which account for multifaceted issues, uncertainties and cope with a wide range of future conditions. To date, several tools and methods to support the design and implementation of adaptive policies have been developed by the research community (e.g. data processing and management, stakeholder analysis and participatory methods, numerical and simulation models, assessment approaches). The paper proposes a (four) step-wise methodology to review, analyze, classify and select existing tools dealing with social, economic and environmental issues. Firstly, existing toolboxes were retrieved. Secondly, an in-depth analysis was performed to classify their potential for the development and implementation of adaptive policies in marine areas. Thirdly, selected tools were included in the ' Database of tools and methods ' of the wider Adaptive Marine Policy Tool Box, designed within the EU-FP7 PERSEUS project (Policy-oriented Environmental Research in Southern European Seas) to support policy makers with the application of an Adaptive Policy Framework. Finally, a review process was performed based on several qualitative criteria and expert judgment, which allowed to identify a set of valuable ' flag tools ' useful to implement each step of the Adaptive Policy Framework. Highlights: A review method to select tools for marine adaptive policy making is described. Tools dealing with socio-economic and environmental issues are critically reviewed. The resulting ' Database of tools and methods' of the PERSEUS AMP TB is presented.